Speech Delay In A 4 Years Old Child - Istiqomah, Selli Deskiyani Nurotul; Magria, Vera; Afrilesa J, Rini (Krinok:Jurnal Linguistik Budaya, 2025)
This research analyses the speech delay by a four-year-old child named Muhammad Lutfi Aziz in Unit 1, Jambi Province, Tebo Regency, Rimbo Bujang District, Perintis Village. The objectives of this study are (1) to explain the forms of speech production in children who experience speech delay (2) To find out the factors of speech delay. The author used a descriptive qualitative method approach to conduct the research. Meanwhile, to analyse the data, the author used the theory from Steinberg (2006) with supporting theory from literature (2010). The results of the study reveal some findings that show that children produce three forms of words at the speech production stage, namely: (1) naming, (2) holophrastic, (3) telegraphic. Based on 24 data found in this study, the author found 3 data of naming words, 12 data of holophrastic words, 9 data of telegraphic words. The results of this study also show that the factor that affects speech delay in this child's speech is the language style of communication when speaking ineffectively, such as parents who do not use clear and correct language.